2020
DOI: 10.21608/ejh.2020.23396.1250
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorating Impact of Phoenix dactylifera L. Leaves Oil Extract on Testicular Toxicity Induced by Gibberellic Acid: Histomorphometric and Immunohistochemical Studies

Abstract: Background: Gibberellic acid is an endogenous plant growth regulator, it has many toxic effects including testicular toxicity. Phoenix dactylifera L. (date palm) is widely used in traditional medicine as anticancer, hepatoprotective, neuroprotective, nephroprotective, gastrointestinal protective and antimicrobial agent. Aim: The present work aimed to clarify the impact of Phoenix dactylifera L. leave oil extract on testicular toxicity induced by gibberellic acid in albino rats. Materials and Methods: Five grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
0
2
0
1
Order By: Relevance
“…reported that oral fisetin administration as a strawberry flavonol revealed resistance to chronic airway disease in mice. Polyphenol agents, such as those in date palm, have been shown to significantly ameliorate cytotoxicity by improving antioxidant and immunity alterations in rat testes ( 47 , 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…reported that oral fisetin administration as a strawberry flavonol revealed resistance to chronic airway disease in mice. Polyphenol agents, such as those in date palm, have been shown to significantly ameliorate cytotoxicity by improving antioxidant and immunity alterations in rat testes ( 47 , 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…Palma Soto, J. A., Parra Acosta, H., & Orduño Cruz, N. Análisis del ácido giberélico desde la cartografía conceptual con enfoque bioético y sustentable | 1-18 Sin embargo, estudios recientes demuestran que el consumo de frutas y verduras tratadas con ácido giberélico induce, en humanos y animales, al estrés oxidativo, alteraciones patológicas del cerebro, pulmón, bazo, estómago, hígado, aparato reproductor y al desarrollo de efectos genotóxicos y cancerígenos (Ahmed & Nofal, 2021).…”
Section: Issn Online 2007-9621unclassified
“…However, previous studies have determined that GA 3 is not exempt of toxicity. The hematotoxicity of GA 3 has been studied using animal models such as rats and mice (Tuluce and Çelik 2006;Muthu et al 2011;Troudi et al 2012a;Ali et al 2021Ali et al , 2022Ahmed and Nofal 2021;Galal et al 2021;Soliman et al 2021aSoliman et al , b, 2022aBushra and Shenouda 2022), hens and quail hens (Elsebai et al 2003b;Elkomy et al 2008;Ismail 2009), and rabbits (El-Sebai 2004). Nevertheless, the impacts of GA 3 on the hematological parameters and erythron profile of fish have not been investigated (Sayed et al 2020).…”
Section: Introductionmentioning
confidence: 99%